Effect of Nigella Sativa on IL-10 in MB Leprosy that Received MDT-WHO Therapy - Febrina Primasanti; Lewie Suryaatmadja; R. Sri Djoko (Faculty of Medicine, Diponegoro University, 2016)
Background: Leprosy, a chronic infectious disease presents a broad clinical spectrum that is correlated with the immunological response of the patient, mainly related to Th1/Th2 cells. IL-10 is a major cytokine produced by Th2 cells inhibits imunostimulatory cytokine produced by Th1 cells. Suppressive effects of IL-10 in monocytes and cytokine synthesis by Th1 cells presumably because IL-10 has a general suppressive effect on immune function. Nigella sativa has a potent potentiating effect on cellular immunity through suppression of Th2 cells and IL-10, resulting in potentiation of Th1 cells. Method: The study design is a randomized pretest and posttest controlled design involving 40 subjects of MB leprosy patients. Serum levels of IL-10 were measured by ELISA. Result: The mean decrease in serum levels of IL-10 (IL-10 delta) in the treatment group (average fell 3.12 pg/ml) is greater than the control group (average rose 0.21 pg/ml), where the difference is statistically significant (p = 0.029). Nigella sativa giving significant correlation with a decrease in IL-10 compared to the control group (p=0.044, OR: 10.23). Conclusion: supplementation of Nigella sativa 3 x 1000 mg for 2 months in patients with MB leprosy can reduce levels of IL-10, thus increasing the cellular immune response in patients with MB leprosy.